Legal Certainty and Implementation of Non-Submission of 25-Year-Old Notary Protocol To The Regional Supervisory Council Based On The Law On The Notary Position - Riyati, Riyati; Martanti, Yurisa; Turhamun, Slamet (Jurnal Indonesia Sosial Sains, 2025)
In today’s society, ethical behavior is increasingly being practiced based on what is permitted or prohibited, rather than on intrinsic values of good and bad. This ethical decline is also observed in corporate environments, where some Christian leaders fail to reflect the character of Christ in their leadership. Such leadership shortcomings are particularly concerning as non-Christian employees often observe and assess the integrity of Christian leaders, who are expected to embody moral and spiritual values. This study aims to explore the role of Christian ethics in shaping effective and spiritually grounded leadership in corporate settings. Using a qualitative research method, the study conducts an in-depth literature analysis of sources related to Christian ethics, leadership principles, and biblical teachings. The findings highlight the importance of the leader-shepherd model, where a Christian leader serves with the heart of a shepherd—caring for employees with love, patience, and sacrifice. This model fosters a spiritually nurturing environment that enhances trust, productivity, and ethical workplace culture. The research implies that integrating Christian ethics into leadership not only strengthens the moral integrity of leaders but also serves as a powerful witness to others in the organization. The study contributes to the discourse on faith-based leadership by offering a biblically grounded perspective on ethical leadership practices in the modern corporate world.